2019
DOI: 10.1186/s12879-019-3896-4
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis-attributable adverse pregnancy outcomes in China: a retrospective cohort analysis of 1187 pregnant women with different syphilis treatment

Abstract: Background Syphilis is responsible for a substantial burden of preventable adverse outcomes in pregnancy. The purpose of this study was to compare the frequency of adverse pregnancy outcomes among syphilis-seropositive women who received different treatment regimens at different times in Guangzhou, China. Methods Pregnant women with syphilis infection who received prenatal and delivery services in Guangzhou between January 2014 and December 2016 were included. Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 23 publications
3
19
0
2
Order By: Relevance
“…The results were consistent with large numbers of other reports [12,17,19,21,[22][23][24][25]. Although in most studies, higher maternal titers were defined as serum titers over 1:8, which were more commonly regarded as risk factors for adverse pregnancy outcomes [19,26], we used a maternal titer threshold of 1:4, and this still greatly increased the occurrence of stillbirth. In our province, maternal titers were checked monthly to keep them under 1:4 or to achieve a 4-fold reduction by delivery.…”
Section: General Characteristicssupporting
confidence: 88%
“…The results were consistent with large numbers of other reports [12,17,19,21,[22][23][24][25]. Although in most studies, higher maternal titers were defined as serum titers over 1:8, which were more commonly regarded as risk factors for adverse pregnancy outcomes [19,26], we used a maternal titer threshold of 1:4, and this still greatly increased the occurrence of stillbirth. In our province, maternal titers were checked monthly to keep them under 1:4 or to achieve a 4-fold reduction by delivery.…”
Section: General Characteristicssupporting
confidence: 88%
“…These results were consistent with other reports looking at stillbirths in pregnant women with syphilis in many countries including the United States [ 12 , 17 , 19 , 21 25 ]. In most studies, high maternal titers, defined as serum titers over 1 : 8, were regarded as a risk factor for adverse pregnancy outcomes [ 19 , 26 ]; however, we used a maternal titer threshold of 1 : 4 to define high titer, and it still correlated with greatly increased occurrence of stillbirth in these women. In the Zhejiang province, maternal titers were checked monthly to keep them under 1 : 4 or to achieve a 4-fold reduction in them by delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Best outcomes are seen when treatment occurs early in pregnancy and >30 days before delivery. [60][61][62] A recent retrospective review found that adverse pregnancy outcomes were significantly lower when maternal treatment occurred before 28 weeks underscoring the importance of early diagnosis and treatment. 62…”
Section: Maternal Treatmentmentioning
confidence: 99%
“…Although the optimal timing of treatment during pregnancy is unknown, there is a direct correlation between treatment timing and adverse pregnancy outcomes, including CS rates. Best outcomes are seen when treatment occurs early in pregnancy and >30 days before delivery 60‐62 . A recent retrospective review found that adverse pregnancy outcomes were significantly lower when maternal treatment occurred before 28 weeks underscoring the importance of early diagnosis and treatment 62 …”
Section: Treatment During Pregnancymentioning
confidence: 99%